Normalized Protein Catabolic Rate Is a Superior Nutritional Marker Associated With Dialysis Adequacy in Continuous Ambulatory Peritoneal Dialysis Patients - Qin, Aiya; Liu, Xiang; Yin, Xiaomeng; Zhou, Huan; Tang, Yi; Qin, Wei (Frontiers in Medicine, 2021)
Introduction: Current knowledge of the relationship between normalized protein catabolic rate (nPCR) and dialysis adequacy is limited. Our study aimed to explore the potential relationship between nPCR and dialysis adequacy. Methods: In this cross-sectional study, we analyzed the association of nPCR with peritoneal dialysis adequacy in 266 continuous ambulatory peritoneal dialysis (CAPD) patients (mean age 48.6±13.1 years; 50.8% male). The patients were divided into two groups: a dialysis inadequacy group (total weekly Kt/V urea < 1.70) and a dialysis adequacy group (total weekly Kt/V urea≥1.70). We then analyzed the correlation between dialysis adequacy and the patients’ primary cause of end-stage renal disease, nutritional and inflammatory markers, and biochemical parameters. Multivariable logistic regression analysis was also used to identify risk factors for inadequate dialysis. Results: We observed a significantly higher level of nPCR (0.98±0.22 vs. 0.79±0.18 g/kg/day, p<0.001) in the dialysis adequacy group, whereas we observed no significant differences among other nutritional markers such as albumin, prealbumin, and transferrin. Correlation analyses revealed that dialysis adequacy was positively associated with residual glomerular filtration rate (rGFR), hemoglobin, serum calcium, and body mass index (BMI), while negatively associated with leak-protein, uric acid, high-sensitivity C-reactive protein, interleukin-6, and serum phosphorus. Furthermore, a logistic regression analysis revealed that gender (male), nPCR<0.815 g/kg/day, overweight, and rGFR<2.43 mL/min/1.73m2 were independent risk factors for inadequate dialysis. Conclusion: Nutritional status is closely associated with dialysis adequacy. Among common nutritional markers, nPCR may be superior for predicting CAPD dialysis adequacy. Gender (male), nPCR<0.815 g/kg/day, overweight, and rGFR<2.43 mL/min/1.73m2 are independent risk factors for dialysis inadequacy in CAPD patients.